2015
DOI: 10.1038/cddis.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Akt phosphorylates Prohibitin 1 to mediate its mitochondrial localization and promote proliferation of bladder cancer cells

Abstract: Bladder cancer (BC) is very common and associated with significant morbidity and mortality, though the molecular underpinnings of its origination and progression remain poorly understood. In this study, we demonstrate that Prohibitin 1 (PHB) was overexpressed in human BC tissues and that PHB upregulation was associated with poor prognosis. We also found that PHB was necessary and sufficient for BC cell proliferation. Interestingly, the overexpressed PHB was primarily found within mitochondria, and we provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 48 publications
2
52
0
Order By: Relevance
“…Subcellular localization and posttranslational modifications may explain the tumor-regulatory activity of PHB1 in different cell types (14,22). In particular, mitochondrial and membrane-associated PHB1 in some cancer cells (such as cervical, lung, and bladder) have been shown to confer anti-apoptotic effects and tumorigenesis (23)(24)(25). In contrast, nuclear PHB1 exhibits proapoptotic or anti-tumorigenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular localization and posttranslational modifications may explain the tumor-regulatory activity of PHB1 in different cell types (14,22). In particular, mitochondrial and membrane-associated PHB1 in some cancer cells (such as cervical, lung, and bladder) have been shown to confer anti-apoptotic effects and tumorigenesis (23)(24)(25). In contrast, nuclear PHB1 exhibits proapoptotic or anti-tumorigenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Although the kinase that phosphorylates the Y259 remains unknown, it is well documented that Akt phosphorylates Phb1 at T258 in non-neuronal contexts. Specifically, Akt may phosphorylate this residue in the cytoplasm, promoting Phb1 mitochondrial translocation 67 or in the lipid raft domain of the plasma membrane to activate the Ras-MAPK and PI3K/Akt pathways 68 . However, previous work in our laboratory demonstrated that the activation state of Akt remains unchanged, and ERK is hyper-activated in the OB from AD subjects 7 , suggesting that OB Phb1 dephosphorylation may be due to a phosphatase action or the inactivation of a specific kinase different than Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Although PHB T258 phosphorylation was abundantly detected in neuroblastoma cell lines, a lack of positive correlation between PHB phosphorylated T258 levels and phosphorylated ERK levels implies that a substantial quantity of this modified PHB is involved in MAPK pathway-independent functions. Indeed, it has been demonstrated that phosphorylation of T258 can induce translocation of PHB from the cytoplasm to mitochondria, where it promotes proliferation in bladder cancer cells (31). Furthermore, because our immunofluorescence analysis demonstrated significant quantities of PHB in the mitochondria of neuroblastoma cells, it is highly likely that mitochondrial PHB plays a significant role in neuroblastoma physiology.…”
Section: Discussionmentioning
confidence: 64%
“…PHB T258 phosphorylation was detected in a panel of 8 neuroblastoma cell lines ( Figure 2C; see complete unedited blots in the supplemental material), though levels of phosphorylated PHB T258 did not correlate with levels of phosphorylated ERK1/2 (Supplemental Figure 2), suggesting that this modified PHB participates in MAPK pathway-independent functions. Indeed, PHB T258 phosphorylation is also reported to facilitate the targeting of PHB to mitochondria (31). The detection of PHB T258 phosphorylation in neuroblastoma cells nonetheless presents the possibility that PHB may augment c-RAF activation in these cells.…”
Section: Phb Is Highly Expressed In Neuroblastomas With 17q Gain Andmentioning
confidence: 99%